Awakening takes place within: a practice-led research through texture and embodiment - Ardern, Sophie; Mortensen Steagall, Marcos (DAT Journal, 2023)
This article explores contextual research and creative design methodologies to understand the relationship between the researcher’s embodied approach and the produced artefact. The question of: ‘How might I honestly depict my own embodied textural world to awaken others?’ frames the project in a way which allows the designer/researcher to produce work organically and honestly. Encompassing different navigational directions and frameworks of information allows personal understanding to pervade through. The ideas of place, nostalgia, storytelling and texture are explored throughout the physical artefacts of a textural archival book ‘Awaken’ and a series of posters. The methodology of a heuristic-led enquiry activated by embodiment enabled the translation into something more significant than an abstract thought. Exploring the contextual knowledge of texture and its multi-sensory ability, nostalgia and embodiment, frames the project in the broader context allowing for a critical work commentary.